“Follow the whistle: physical activity is calling you”: evaluation of implementation and impact of a Portuguese nationwide mass media campaign to promote physical activity - Silva, Marlene Nunes (2021)
To raise perceived capability (C), opportunity (O) and motivation (M) for physical activity (PA) behaviour (B) among adults, the Portuguese Directorate-General of Health developed a mass media campaign named “Follow the Whistle”, based on behaviour change theory and social marketing principles. Comprehensive formative and process evaluation suggests this media-led campaign used best-practice principles. The campaign adopted a population-wide approach, had clear behavioural goals, and clear multi-strategy implementation. We assessed campaign awareness and initial impact using pre (n = 878, 57% women) and post-campaign (n = 1319, 58% women) independent adult population samples via an online questionnaire, comprising socio-demographic factors, campaign awareness and recall, and psychosocial and behavioural measures linked to the COM-B model. PA was assessed with IPAQ and the Activity Choice Index. The post-campaign recall was typical of levels following national campaigns (24%). Post-campaign measures were higher for key theory-based targets (all p < 0.05), namely self-efficacy, perceived opportunities to be more active and intrinsic motivation. The impact on social norms and self-efficacy was moderated by campaign awareness. Concerning PA, effects were found for vigorous activity (p < 0.01), but not for incidental activity. Overall the campaign impacted key theory-based intermediate outcomes, but did not influence incidental activity, which highlights the need for sustained and repeated campaign efforts.